2019
DOI: 10.1177/1054773819865874
|View full text |Cite
|
Sign up to set email alerts
|

The Application of PRECEDE Model on Preventing Osteoporosis in Women

Abstract: The aim of this study is investigating the efficiency of educational intervention based on PRECEDE model on promotion of osteoporosis prevention behaviors in women. This quasi-experimental study was conducted on 200 women registered in two health centers of Fasa city, Fars province, Iran in 2017 to 2018. A questionnaire including items evaluating demographic information and PRECEDE model constructs was used for measuring nutrition and walking performance of studied women in osteoporosis prevention before and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
2
1
0
Order By: Relevance
“…In a study by Welsh et al, which examined the effect of educational intervention based on the TPB on low-salt diet among the patients with heart failure in 2012, the results showed that after 6 months, dietary sodium in the experimental group significantly decreased compared to the control group [ 81 ]. The results of other studies were consistent with the results of this study [ 82 – 84 ].…”
Section: Discussionsupporting
confidence: 93%
“…In a study by Welsh et al, which examined the effect of educational intervention based on the TPB on low-salt diet among the patients with heart failure in 2012, the results showed that after 6 months, dietary sodium in the experimental group significantly decreased compared to the control group [ 81 ]. The results of other studies were consistent with the results of this study [ 82 – 84 ].…”
Section: Discussionsupporting
confidence: 93%
“…a current investigation by Bazrpour et al [23], there was a significant increase in knowledge immediately and one month after the intervention. The results of our study were consistent with the result of studies by Wang et al [14], Khani Jeyhooni et al [24], Koc et al [25], and Kaewchi et al [26]. Using group discussion, brainstorming, and participating individuals and peers pave the way to share information and experiences.…”
Section: Discussionsupporting
confidence: 91%
“…Our results were consistent with those of other studies because patients' self-care benefits greatly from the support of medical experts, family, and friends. [16,30,31]; with the difference in the mentioned studies the sample size and the number of training sessions were less, and also in the study of Solhi et al, they used the self-management theory in addition to the Persed model for educational intervention. The enabling elements significantly changed after the educational intervention due to improvements in knowledge, attitude, self-efficacy, and reinforcing factors.…”
Section: Discussionmentioning
confidence: 99%